THE RESPONSIVINESS OF REGIONAL WATER UTILITY COMPANY (PDAM) TIRTA MOEDAL OF SEMARANG CITY IN HANDLING THE PUBLIC COMPLAINTS - Nia Pratiwi; Susi Sulandari (Journal of Public Policy and Management Review, 2019)
Water services is one of many service sectors that have to fulfilled by the government on all region in Indonesia, includes Semarang City Government. The efforts by Semarang City Government to fulfill the clean water requirement for public is by optimizing the function of PDAM Tirta Moedal of Semarang City. The purpose of this research is to describe dan analyze the responsiviness of PDAM of Semarang City in handling the public complaints and to identify the support factors and the obstacle factors that influence the responsiveness of PDAM of Semarang City in handling the public complaints which is this research has been done by using descriptive qualitative research methode. The result showed that the responsiveness of PDAM of Semarang City in handling the public complaints was not yet responsive because there are some responsiveness phenomenon that cannot be fulfilled by PDAM of Semarang City in performing a responsive complaint services. Then, there is an obstacle factors in the improvement of the responsiveness PDAM of Semarang City in handling the public complaints that is organizational resource factor and technical guidance factor. Meanwhile, the supporting factor is the existence of Standard Operating Prosedure (SOP). The advice for Regional Water Utility Company (PDAM) of Semarang City to improve the responsiveness in handling the public complaints is to do open recruitment of new employees, do capability training for the employees, also to arrange the Citizen Charter in providing complaint services.